Evolutionary Epistemology and Plato’s Knowledge - Masís Iverson, Katherine (2014)
This paper briefly compares evolutionary epistemology and knowledge according to Plato. First, Plato’s approach to knowledge as portrayed in his Theaetetus is described, followed by Nathalie Gontier’s characterization of evolutionary epistemology. Finally, points of agreement and disagreement between Plato’s epistemology and evolutionary epistemology are discussed.